2021
DOI: 10.1515/abitech-2021-0003
|View full text |Cite
|
Sign up to set email alerts
|

Discoverability in (a) Crisis

Abstract: The coronavirus pandemic has exposed a host of issues with the current scholarly communication system, one aspect being the discoverability of scientific knowledge. Observing the many shortcomings of discovery workflows in the course of COVID-19 confirms that discoverability itself is in crisis. In this article, we analyze the discoverability crisis and its root causes. We introduce open discovery infrastructure as a promising approach for the development of innovative discovery solutions. We present several e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…This field of tension and the related concern about the state of the scientific public sphere is becoming manifest in the widespread criticism of current publication strategies (e.g., 'salami slicing', that is, dividing findings among as many individual articles as possible), patterns of reception (e.g., limiting reading to a few 'top tier journals') and citation practices (e.g., overciting and citing according to the principle of recency rather than relevance). To navigate this tension, new text genres (e.g., meta-reviews') and technological methods for personalized search and visualization of scholarly sources are emerging, such as 'discovery infrastructures' and 'knowledge maps' (Kraker et al 2021).…”
Section: Structural Transformation Of the Scientific Public Spherementioning
confidence: 99%
See 1 more Smart Citation
“…This field of tension and the related concern about the state of the scientific public sphere is becoming manifest in the widespread criticism of current publication strategies (e.g., 'salami slicing', that is, dividing findings among as many individual articles as possible), patterns of reception (e.g., limiting reading to a few 'top tier journals') and citation practices (e.g., overciting and citing according to the principle of recency rather than relevance). To navigate this tension, new text genres (e.g., meta-reviews') and technological methods for personalized search and visualization of scholarly sources are emerging, such as 'discovery infrastructures' and 'knowledge maps' (Kraker et al 2021).…”
Section: Structural Transformation Of the Scientific Public Spherementioning
confidence: 99%
“…Systems for filtering scientific information draw on both the metadata and the full digital texts of scientific articles. The more freely metadata and full texts are available, the better they can be read, evaluated, processed and combined with data sets from other filter systems (Kraker et al 2021).…”
Section: Unintended Consequences For the Scientific Public Spherementioning
confidence: 99%
“…The sheer number presents us with two problems: finding relevant publications and synthesizing the knowledge. These problems are of course not unique to the science of hydrology (Kraker et al, 2021). However, they are particularly pressing in hydrology and despite repeated discussion of the problems, have not been addressed to date.…”
Section: A Flood Of Articles or A Wealth Of Knowledge?mentioning
confidence: 99%
“…Overall, while the literature paints a picture of GS as a service more “equitable” than citation databases, it is difficult to assume that it offers a full and transparent solution. Although offered for free, GS still remains a closed service to a larger extent ( Coiffait, 2019 ; Kraker et al , 2021 ). Indeed, several authors have pointed to the lack of transparency offered about how the service algorithms work, which to a large extent mirrors what happens with the main search engine Google (e.g.…”
Section: Why Google Scholar Is Not a Complete Discovery Platformmentioning
confidence: 99%
“…While this interface was certainly innovative at that time, Google has since stopped integrating the new developments from its general web search into GS. In fact, it has been shown that the interface has hardly been updated in the last ten years ( Kraker et al , 2021 ). This means that Google has not invested enough in GS to keep up with the growing research output.…”
Section: Introductionmentioning
confidence: 99%